Factors Affecting Work Engagement - Justine Tanuwijaya; Anreas Wahyu Gunawan; Mega Puraswati (Business and Entrepreneurial Review, 2022)
The purpose of this study was to explore the influence of supervisor support, job characteristics, authentic leadership on employees’ work engagement  of PT Burangkeng  Maju Tehnik. Based on literature review a conceptual framework is proposed that links all independent variables to work engagement. The mode of was tested on sample of 125 employees working at PT Burangkeng Maju Tehnik. The framework was tested with multiple regression approach. The results of this study show that there is a positive effect  supervisor support, job characteristics, and authentic leadership on work engagement.. It is suggested that leaders increase supervisor support by providing assistance to their subordinates related to work. For  improving job characteristics, leaders should notice to job significance. To enhance authentic leadership, leaders should  focus on relational transparency by building transparent and open relationships with employees. To strengthen work engagement, leaders ought concern to cognitive engagement by motivating employees. Keywords: Authentic Leadership; Job Characterictic; Supervisor Support; Work Engagement